Knowledge and knower structures and recontextualising logics in an accounting curricular framework - Lubbe, Ilse (School of Education, 2022)
Accountants require specialised knowledge, competencies and skills to deliver quality services. In the modern business environment, this can take the form of financial accounting, reporting, planning and decision-making. This thesis identifies the need for change in the accounting curriculum to meet the requirements of the professional accountant of the future. In response to this need, a framework is developed for the design of a holistic academic curriculum in accounting that includes knowledge, competencies and skills. By drawing on the sociology of knowledge, this study identifies the production sites and analyses the knowledge and knower structures of accounting, and describes how knowledge is rearranged and transformed to become pedagogic discourse. These findings, including the design of the framework, are illustrated using a case study of specialised accountancy knowledge. The study contributes to the field of accounting education in that the framework demonstrates the design principles required to achieve an incremental and integrated approach for the selection, ordering and pacing of specialised accounting knowledge.